Integrating Al-Islam Kemuhammadiyahan Values into Linear Algebra E-Module: Analysis of Development Needs - Novia Ariyanti; Cindy Taurusta; Anis Farihah (Indonesian Journal of Cultural and Community Development, 2023)
This study addresses the impact of the COVID-19 pandemic on student morale and religious values by exploring educational reforms, with a focus on integrating Al-Islam Kemuhammadiyahan values into mathematics education. The unique integration of these values within the Linear Algebra e-module at Muhammadiyah University of Sidoarjo, specializing in Informatics, sets it apart. Employing research and development (R&D) methods with the ADDIE model, this study delves into the analysis phase, using an online questionnaire to collect data from 20 third-semester Informatics students. Employing descriptive qualitative analysis, the study unveils crucial insights into the development needs of a linear algebra e-module that incorporates Al-Islam Kemuhammadiyahan values, thereby contributing to enriched pedagogical strategies in higher education. Highlight: Pandemic Impact: This study addresses the influence of the COVID-19 pandemic on student morale and religious values, emphasizing the need for educational reforms. Values Integration: Focusing on Al-Islam Kemuhammadiyahan values, the study uniquely integrates them into the Linear Algebra e-module at Muhammadiyah University, enhancing the curriculum's distinctiveness. Methodology Insight: Utilizing R&D methods and the ADDIE model, the research delves into the analysis phase, employing online questionnaires to gather data from third-semester Informatics students. Employing descriptive qualitative analysis, the study provides valuable insights into developing a values-incorporating linear algebra e-module, contributing to enhanced pedagogical strategies in higher education. Keyword: COVID-19 Pandemic, Student Morale, Religious Values, Educational Reforms, Al-Islam Kemuhammadiyahan Integration